Framework for Block-Chain Deployment in Assembly of an Air-Craft or a SpaceCraft. Issue 1 (2021) - Cohen, Yuval; Nabrzyski, Jarek; Taylor, Ian
Abstract: The final assembly of an aircraft or a spacecraft is a rigorous task that requires full traceability of the parts installed, their fabrication processes, and the assembly work. This is also the case for each of its sub-assemblies. Safety and security go hand in hand in the production of these flying machines, and even more so for satellites and space-shuttles. The many parts and sub-assemblies that compose the final spacecraft, make full traceability a challenging fit, that is almost unsurmountable. Such traceability is not existent today and must be based on documentation of most assembled parts, assembly tasks, and inspection tasks that compose the full spacecraft. In addition, security measures are needed to prevent hostile hacking and unauthorized approach to the space-craft assembly documentation. This paper describes a framework that harnesses smart-contract and blockchain technology to offer traceable and secure documentation of the assembly process. The concept of a Bill-Of-Assembly (BOA) is introduced which incorporates data from the bill of materials, the bill of operations and processes, and the bill of resources (machines and/or operators). The paper describes the use of the BOA with smart-contract and blockchain technology for getting full traceability, safety, and security for the spacecraft. Finally, we show that this BOA data structure could be the backbone of a digital twin of the spacecraft. Future research could extend the proposed approach to other assembly processes such as automotive assembly lines.